2020
DOI: 10.1590/0034-7167-2019-0109
|View full text |Cite
|
Sign up to set email alerts
|

Pain assessment in pediatrics

Abstract: Objectives: to investigate how the pain assessment and management process in pediatric patients is performed and suggestions for its improvement. Methods: exploratory, qualitative study. Nine professionals from the nursing team of a pediatric hospital unit in Porto Alegre/RS participated in the study. A sociodemographic questionnaire and semi-structured interviews were used with content analysis. Results: the results reinforced the importance of pain assessment with family participation and the need to use t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
3
0
2
Order By: Relevance
“…Individuals who present pain and receive care from a skilled nursing team that makes use of tools for pain measurement and assessment have positive results in their pain management and receive individualized treatment options for their case. Therefore, the use of scales to measure, systematize care, and improve pain assessment is crucial as long as the healthcare team is trained to do so (32) . In this review, the two scales most mentioned among the included studies were: NRS (53.84% of the sample) and VAS (30.76%).…”
Section: Discussionmentioning
confidence: 99%
“…Individuals who present pain and receive care from a skilled nursing team that makes use of tools for pain measurement and assessment have positive results in their pain management and receive individualized treatment options for their case. Therefore, the use of scales to measure, systematize care, and improve pain assessment is crucial as long as the healthcare team is trained to do so (32) . In this review, the two scales most mentioned among the included studies were: NRS (53.84% of the sample) and VAS (30.76%).…”
Section: Discussionmentioning
confidence: 99%
“…Os indivíduos que apresentam dor e recebem os cuidados de uma equipe de enfermagem capacitada que faz uso de ferramentas para mensuração e avaliação da dor possuem resultados positivos no manejo da sua dor e recebem opções de tratamento individualizadas para o seu caso. Portanto, a utilização de escalas para a mensuração, sistematização da assistência e melhoria da avaliação da dor é crucial desde que a equipe de saúde esteja capacitada para isso (32) . Nesta revisão, as duas escalas mais 8 de Estratégias não farmacológicas na analgesia de adultos e idosos em procedimentos endovasculares: revisão de escopo Santos KVG, Rocha MA, Dantas JKS, Araújo SCM, Dantas DV, Dantas RAN.…”
Section: Discussionunclassified
“…Also regarding pain management in the pediatric context, in situations where communication is impaired, the interaction between the health team and the family members is more than necessary. Such relationship facilitates decision-making and the course of action, and the parents' knowledge about their child and this view, together with the professionals, especially nurses, facilitates identification and relief of discomfort (12) .…”
Section: Discussionmentioning
confidence: 99%
“…It is noted that this decision became a limitation in data analysis and exerted an impact on interpretation of the results, as the scale was not applied in full; however, since this is a pioneering study, it was decided to keep it, as the behavioral pattern could be assessed. It is suggested that, at another time when using VR glasses, the numerical scale (12) is associated with the use of the FLACCr scale (10) in order to better consolidate the results. At the end of the procedure, the children were taken back in their beds.…”
Section: Data Collection Period and Systematic Proceduresmentioning
confidence: 99%